Highly Fluorescent 2‐Aminopurine Derivatives: Synthesis, Photo‐physical Characterization, and Preliminary Cytotoxicity Evaluation. Issue 16 (5th April 2023) - Gonçalves, Jorge M.; Gonçalves, João N. D.; Pêra, Ana S.; Senhorães, Nádia R.; Rodrigues, Ana Rita O.; Oliveira, Rui; Coutinho, Paulo J. G.; Castanheira, Elisabete M. S.; Dias, Alice M.
Abstract: New fluorescent nucleobase analogues (FBAs) are emerging as extraordinarily useful tools for DNA labelling technologies. The highly fluorescent adenine analogue 2‐aminopurine (2AP) is still the most used within the few hundreds of newly FBAs synthesized, but its excitation in the UV region demands for high energy sources endangering living cells. New and highly fluorescent 2AP derivatives, 2‐amino‐6‐cyanopurines, were obtained using simpler but efficient synthesis method. All the new compounds exhibit advantageous photophysical properties over 2AP, showing absorption and emission bands ranging the visible region (blue‐green region), high fluorescence quantum yields and Stokes' shifts, especially in non‐protic organic solvents. Density Functional Theory calculations (DFT) of electronic and vibrational structure were performed, allowing to predict absorption and emission spectra. In addition, these 2‐amino‐6‐cyanopurines exhibit little to no toxicity in assays using yeast cells. Abstract : Highly fluorescent 2‐aminopurine (2AP) derivatives, 2‐amino‐6‐cyanopurines, were obtained using a new and simple synthesis method. All the new compounds exhibit advantageous photophysical properties over 2AP, emitting in the blue/cyan spectral region, and little or no toxicity in assays using yeast cells. These compounds are valuable candidates for fluorescence studies in biological systems.